Exploring the possibilities of automated feedback for third level students - Ian Clancy; Ann Marcus-Quinn (Firenze University Press, 2019)
There are a multitude of methods of providing third level students with feedback on their performance. Feedback can take many forms, from handwritten comments, to individual verbal feedback delivered face to face, and some educators are providing recorded audio feedback delivered using an institutional Virtual Learning Environment. One of the challenges at third level is providing substantive and constructive formative and/or terminal feedback in a timely fashion. Students are becoming more self-directed in terms of their learning and they are becoming more demanding regarding feedback. This paper discusses the use of a free open source solution (Auto Multiple Choice, AMC) to provide constructive feedback to students in an effective and timely manner. This method of automated assessment feedback has been used by faculty in Physics at the University of Limerick to reduce the turnaround time in making comments available to students since 2014. The experience of using AMC has also resulted in a number of unanticipated results around student motivation and prediction of exam performance which are also discussed.   Esplorare le possibilità di feedback automatizzato per gli studenti universitari. Esistono numerosi metodi per fornire feedback agli studenti universitari sulle loro prestazioni. Il feedback può assumere molte forme, dai commenti scritti a mano al feedback verbale individuale in presenza. Alcuni educatori forniscono feedback audio registrati usando un ambiente di apprendimento virtuale istituzionale. Una delle sfide universitarie consiste nel fornire un feedback formativo e/o finale in modo tempestivo. Gli studenti stanno diventando semore più "apprendisti" auto-diretti e stanno diventando sempre più esigenti in termini di feedback. Il contributo riflette sull'uso di un dispositivo gratuito open source (Auto Multiple Choice, AMC) per fornire feedback costruttivi agli studenti in modo efficace e tempestivo. Il metodo di feedback di valutazione automatizzato è stato utilizzato dalla facoltà di Fisica dell'Università di Limerick per ridurre i tempi di consegna dei commenti disponibili per gli studenti dal 2014. L' utilizzo dell'AMC ha inoltre consentito di realizzare una serie di risultati imprevisti sulla motivazione degli studenti e sulla previsione delle prestazioni degli esami, discussi nel paper.